A violent masterpiece : a novel - Harper, Jordan (Mulholland Books / Little, Brown and Company, 2026)
"A city ready to explode: A Hollywood pedophile is arrested, and is ready to tear down the city to get his freedom. A young woman goes missing-and men in black rubber gloves who look like cops clean out her apartment in the middle of the night. And the serial killer known as the LA Ripper is on the loose, leaving tragic/graphic/brutal crime scenes in his wake. Three people trying to keep their heads above the dirty water will find themselves coming together to unite these strands into one enormous, unspeakable crime ... Jake Deal is a gonzo live-streaming nightcrawler, beaming the city's chaos straight to his audience of blood-hungry subscribers, giving them the view from the top of the mushroom cloud-until a job he can't refuse drags him back into his old life of Hollywood glamour, drugs, sex and sleaze. Armed with cameras and hidden mics, he'll infiltrate private clubs, gather high-class dirt-and stumble onto a conspiracy woven into the center of LA's most powerful men, who call themselves 'The Kids in the Candy Store.' Doug Gibson is a street lawyer, who fights for his clients against the army of cops, prosecutors and judges-he is the knife they bring to the gunfight. But when he's hired by a Hollywood pedophile ready to sell out his friends for a chance for freedom, he'll take on a fight bigger than he could have imagined. And when his client 'commits suicide' in prison, Gibson will have to stop being a weapon-and become a warrior. Kara Delgado works for an underground private concierge company-a make-a-wish foundation for the terminally rich. She scores drugs, makes connections, and plans multi-million dollar sex parties.She has learned the secret truth of this world: there are no rules, only prices. Her best friend Phoebe has gone missing, and Kara's the only person who knows that Phoebe's place was wiped clean of evidence by men in black rubber gloves. But when she begins to unravel the mystery of what happened to Phoebe, and its connection to the killer known as the LA Ripper, it will drag her into the dark heart of the city. As Jake, Doug and Kara all investigate these crimes, they'll encounter ketamine-addled sitcom stars, bloody riots, homeless gangsters, a killer cop on death row, secret vaults in Beverly Hills, tech-bro orgies, medical cannibals, true crime junkies, private security wet-work teams, reality shows, street takeovers, car chases, coyotes, a sadistic Tarzan, and a three day, fifty million dollar wedding, before everything is revealed and they must each make their choice about how to fight back in this violent world before the bloody, blazing conclusion."--